Corticosteroid treatment and prognosis in pulmonary eosinophilia. Issue 11 (November 1989) - Capewell, S; Chapman, B J; Alexander, F; Greening, A P; Crompton, G K
Abstract : The acute and long term responses to corticosteroid treatment in 65 patients with pulmonary eosinophilia have been reviewed. Of the 247 episodes of pulmonary eosinophilia that were documented during a median follow up period of 14 years, 186 were treated with prednisolone. Complete clearing of chest radiographic infiltrates occurred in 65% of the 247 episodes, partial clearing in 25%, and no response in 9%. Blood eosinophil counts were monitored during 194 episodes and returned to normal in 72%, decreased in 19%, and remained raised in 9%. Complete radiological clearing and a reduction in blood eosinophil counts were more common in episodes treated with prednisolone. Long term prednisolone was given to 28 of the 33 patients with allergic bronchopulmonary aspergillosis (mean 7.4 mg/day for 11 years) and to 29 of the 32 "non-aspergillosis" patients (mean 8.1 mg/day for 4.6 years). Initial pulmonary function, measured between episodes, was worse in patients with allergic aspergillosis than in those without (mean % predicted: FEV1 57% v 83%, vital capacity (VC) 76% v 88%). During a mean follow up period of 12 years neither group displayed further decline in FEV1 or VC.